Lynx canadensis - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2009)
22. Canadian Lynx Lynx canadensis French: Lynx du Canada / German: Kanadischer Luchs / Spanish: Lince canadiense Taxonomy. Lynx canadensis Kerr, 1792, Canada. Present species and L. lynx sometimes considered conspecific. Two subspecies recognized. Subspecies and Distribution. L. c. canadensis Kerr, 1792 — mainland Canada and N USA. L. c. subsolanus Bangs, 1897 — NE Canada (Newfoundland I). Descriptive notes. Head-body 76.2-106. 7 cm, tail 5-12. 7 cm; weight 5.0-17. 3 kg. Little geographic variation in size but males larger and heavier than females. In Newfoundland the mean weight of adult males was 10-7 kg (range 6.3-17. 3 kg) versus 8-6 kg (range 5.0-11. 8 kg) for adult females. The fur, except for the undersides,is unspotted and the background color is buff-gray. Undersides are white and mottled with black spots. The long, pale-colored belly fur is valued by the garment industry. The winter fur of cats in Newfoundland is thick and silvered over with hoary tips, giving the cat a uniform gray color. In other areas winter pelts are more grayish-brown mixed with buff or pale brown. There are no records of melanistic cats but there are a few records of “blue lynx ”. The cat’s cheeks are fringed with a ruff of long hair. Backs of the ears are black at the base and the tips are adorned with an elongated tuft of black hair. Tail tip is completely black, which distinguishes it from the Bobcat, in which thetip is dark only on the dorsal half. Paws are covered with long, dense fur and feet are large and snowshoe-like, which provides additional support in soft snow. Cat is muscular, leggy, and stands about 48-56 cm high at the shoulder. Hindlimbs are longer than front, giving the cat a tipped-forward appearance. Habitat. A variety of forest types within the broad belt of boreal forest that stretches from Alaska to Newfoundland. They are also found in the coniferous forests of the northern Cascade Mountains of Washington and the Rocky Mountains of north-east Utah and central Colorado at elevations above 2700 m. Prey almost ...